Corporate Social Responsibility After Disaster - Susan S. Kuo; Benjamin Means (Washington University Law Review, 2012)
In recent years, corporations have devoted substantial resources to disaster relief worldwide. For instance, Wal-Mart garnered favorable attention for its contributions in New Orleans and the Gulf Coast after Hurricane Katrina. According to company press releases, Wal-Mart recently gave hundreds of thousands of dollars for disaster relief in Brazil following a flood, and it has pledged millions in support of Japan in the wake of the tsunami. Large corporations have not only the economic resources, but also the logistical capacity and operational expertise to make a difference in the first terrible days after a disaster. However, commentators disagree about how best to harness corporate resources to support disaster relief efforts. This is not a new issue; the disaster law and policy discussion is only the latest iteration of a longstanding debate concerning the proper role of the corporation in society. Broadly speaking, there are two frameworks for assessing corporate social responsibility: a “classical” framework that treats non-shareholder interests as outside the corporation’s proper concern, and a “progressive” framework that encourages corporations to pursue a broader social agenda. According to the classical framework, corporations contribute to society by maximizing profits for their shareholders. On this view, giving managers discretion to use corporate resources for other purposes only exacerbates agency costs between the managers and the shareholders who entrust their capital to the corporation. By contrast, the progressive framework emphasizes that corporations owe their existence to the state and benefit from limited liability and other special protections and thus concludes that corporations have a special duty to serve a broader community of stakeholders.